A collaboration mechanism among agents in the agent-based guidance system. (1st January 2002) - Takaoka, Ryo; Okamoto, Toshio
Recently, educational systems based on the agent model of architecture have been developed. Such agents are used to provide a variety of functions to students. These agents perform individual tasks yet collaborate with other agents to achieve a common goal. Using these agents, it is possible that the educational system can dynamically determine its behaviour in various situations better than a typical intelligent tutoring system. The purpose of this study is to propose a methodology for the design of an educational system based on an agent model of architecture. This paper describes the framework of the agent-based guidance system and the method for representing communication primitives and protocols. Moreover, we explain an example of collaboration among the agents.